2008
DOI: 10.1074/mcp.m700273-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Metabolomic and Proteomic Phenotypes

Abstract: Statistical mining and integration of complex molecular data including metabolites, proteins, and transcripts is one of the critical goals of systems biology (Ideker, T., Galitski, T., and Hood, L. (2001) A new approach to decoding life: systems biology. Annu. Rev. Genomics Hum. Genet. 2, 343-372). A number of studies have demonstrated the parallel analysis of metabolites and large scale transcript expression. Protein analysis has been ignored in these studies, although a clear correlation between transcript a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(58 citation statements)
references
References 83 publications
1
57
0
Order By: Relevance
“…For instance there are many metabolomics pathways regulated at the post-transcriptional level (Kaplan et al 2007). The integrated omic studies are specially promising for ecological studies since they make possible discerning between genotype dependent and independent response to environmental changes for multiple characters at once (Pena et al 2010;Wienkoop et al 2008). This provides an overview of the short-, medium-and long-term responses to environemental changes and their integrative relationships.…”
Section: Metabolomics Coupled With Other Omics Approachesmentioning
confidence: 99%
“…For instance there are many metabolomics pathways regulated at the post-transcriptional level (Kaplan et al 2007). The integrated omic studies are specially promising for ecological studies since they make possible discerning between genotype dependent and independent response to environmental changes for multiple characters at once (Pena et al 2010;Wienkoop et al 2008). This provides an overview of the short-, medium-and long-term responses to environemental changes and their integrative relationships.…”
Section: Metabolomics Coupled With Other Omics Approachesmentioning
confidence: 99%
“…Some general statistical tools, such as unsupervised multivariate exploratory data mining, correlation network topology analysis, pattern recognition, principal components analysis and sparse partial least squares regression have been used for integrative proteomic and metabolomic analysis (Weckwerth et al, 2004;Morgenthal et al, 2006;Weckwerth & Morgenthal, 2005;Morgenthal et al, 2007;Wienkoop et al, 2008;Lê Cao et al, 2008). The results demonstrated that good pattern recognition and association identification through proper statistical tools are important for the biological interpretation.…”
Section: Methodologies For Integrated Proteomics and Metabolomicsmentioning
confidence: 99%
“…The upregulation of ADF under drought and salt stress indicates that this protein might be associated with dynamic reorganization of the cytoskeleton during drought stress. Redox proteins such as glutathione dehydrogenase (At1g19570) are affected in stress regulation (Morgenthal et al 2007 ;Wienkoop et al 2008 ) .…”
Section: Proteomic Approachmentioning
confidence: 99%